The interactions between gut microbiota and bioactive ingredients of traditional Chinese medicines: A review. (July 2020) - Gong, Xue; Li, Xue; Bo, Agula; Shi, Ru-Yu; Li, Qin-Yu; Lei, Lu-Jing; Zhang, Lei; Li, Min-Hui
Graphical abstract: The gut microbiota decomposes the ingredients in TCM into secondary metabolites with high biological activity, promotes the entry of medicines into the circulation, and has a beneficial effect on pathological sites. At the same time, the ingredient of TCM can well change the composition and structure of the gut microbiota, thereby realising the function of diseased organ/tissues through the systemic action of the gut microbiota. Abstract: In recent years, the interaction between the bioactive ingredients of traditional Chinese medicine (TCM) and gut microbiota has been a focus of many studies. When TCM enters the digestive tract, some bioactive ingredients are not absorbed into the gut well thus leading to low bioavailability. Ingredients of TCM are metabolised, or biotransformed by gut microbiota, thereby producing new bioactive molecules, and promote medicine absorption into the circulation. At the same time, the ingredients of TCM effect the composition and structure of gut microbiota, thereby influencing the remote function of diseased organs / tissues through the systemic action of the gut microbiota. In this review, we summarise the gut microbiota-mediated metabolism of flavonoids, alkaloids, terpenoids, saponins, polysaccharides, phenylpropanoids, and organic acids, along with a discussion on the metabolites formed and the biotransformation pathways involving various enzymes. We also highlight the importance of bioactive ingredients of TCM in regulating gut microbiota.